KESIAPAN SMKN 1 PANCUNG SOAL DALAM MENGHADAPI PEMBELAJARAN DI ERA NEW NORMAL - Ramadhani Ramadhani; Efendi Efendi; Revi Handayani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to determine the readiness of SMKN 1 Pancung Soal in dealing with learning in the new normal era, the obstacles faced by SMKN 1 Pancung Soal in dealing with learning in the new normal era and the solutions of SMKN 1 Pancung Soal in dealing with learning in the new normal era. This type of research by its nature is a qualitative research. Data obtained through observation, interviews and documentation. The subjects of this qualitative research were teachers and principals at SMKN 1 Pancung Soal. The results showed that elementary school readiness in facing learning in the new normal era with school readiness as learning readiness which includes health screening protocols, application of health protocols, applying several learning methods, communication and collaboration in the use of technology. The obstacles faced by schools in dealing with learning in the new normal era are changes in curriculum, students, teachers, parents, and completeness of facilities and infrastructure, innovation and implementation. The solution that can be done by schools in facing the constraints of school readiness in learning in the new normal era is to recognize the conditions that occur, focus on the condition of students and parents